2007
DOI: 10.1051/m2an:2007027
|View full text |Cite
|
Sign up to set email alerts
|

A topological asymptotic analysis for the regularized grey-level image classification problem

Abstract: Abstract. The aim of this article is to propose a new method for the grey-level image classification problem. We first present the classical variational approach without and with a regularization term in order to smooth the contours of the classified image. Then we present the general topological asymptotic analysis, and we finally introduce its application to the grey-level image classification problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…The model we proposed in this note is an extension to color images of the method introduced in [4] and [3]. The numerical tests show that our method can successfully remove the noise and preserve the global features of a color image.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The model we proposed in this note is an extension to color images of the method introduced in [4] and [3]. The numerical tests show that our method can successfully remove the noise and preserve the global features of a color image.…”
Section: Resultsmentioning
confidence: 95%
“…We note here that the topological gradient process requires only 3 resolutions of a PDE (direct and adjoint with c = c 0 and then direct with c = c 1 ) for each channel. Moreover, using a discrete cosine transform for the two first resolutions (c = c 0 ) and then a preconditioned conjugate gradient for the third one (c = c 1 ), the authors already showed that the computational cost of this algorithm is in O(n. log(n)) where n is the size of the image [4,5,3]. …”
Section: Application Of the Topological Asymptotic Expansion To Colormentioning
confidence: 99%
See 2 more Smart Citations
“…By enlarging the set of admissible solutions, relaxation increases the instability of the restoration process and this could explain why the topological gradient method is so efficient. Then, using the same idea, the authors generalize in Auroux et al (2007) the topological gradient approach for classification problems and propose an extension to an unsupervised classification. A natural application of this idea is the problem of segmentation: since the identification of the main edges of the image allows us to preserve them and smooth the image outside the edges, then if the conductivity c outside edges is large enough, the regularized image is piecewise constant and provides a natural segmentation of the image.…”
Section: Introductionmentioning
confidence: 99%